Analisis Proses Pada Senayan Library Information Management System (SLIMS) Cendana Berbasis Data Flow Diagram (DFD) Di Perpustakaan Universitas Kristen Duta Wicana Yogyakarta - Abdul Rahman Simatupang; Syifaun Nafisah (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2020)
This research aimed to analyze the process of cendana senayan library information management system (SLIMS) based on data flow diagram (DFD) in Duta Wicana Christian University.. Methodology of this research used field research and the object of this research is cendana senayan library information management  system (SLIMS). Finding of this research is all of the features in SLIMS Cendana such as borrowing process, return process, library member registration process, importing book data collection process, and imposing sanctions on library users who are late returning the books can be cover with Data Flow Digram (DFD), so it can be easier for librarians to conduct library processing activities and in the information retrieval in library.